Cysteinyl Leukotrienes in Eosinophil Biology: Functional Roles and Therapeutic Perspectives in Eosinophilic Disorders - Thompson-Souza, Glaucia A.; Gropillo, Isabella; Neves, Josiane S. (Frontiers in Medicine, 2017)
Cysteinyl leukotrienes (cysLTs), LTC4, and its extracellular metabolites, LTD4 and LTE4, have varied and multiple roles in mediating eosinophilic disorders including host defense against parasitic helminthes and allergic inflammation, especially in the lung and in asthma. CysLTs are known to act through at least 2 receptors termed cysLT1 receptor (CysLT1R) and cysLT2 receptor (CysLT2R). Eosinophils contain a dominant population of cytoplasmic crystalloid granules that store various preformed proteins. Human eosinophils are sources of cysLTs and are known to express the two known cysLTs receptors (CysLTRs). CysLTs can have varied functions on eosinophils, ranging from intracrine regulators of secretion of granule-derived proteins to paracrine/autocrine roles in eosinophil chemotaxis, differentiation and survival. Lately, it has been recognized the expression of CysLTRs in the membranes of eosinophil granules. Moreover, cysLTs have been shown to evoke secretion from isolated cell-free eosinophil granules operating through their receptors expressed on granule membranes. In this work, we review the functional roles of cysLTs in eosinophil biology. We review cysLTs biosynthesis, their receptors, and argue the intracrine and paracrine/autocrine responses induced by cysLTs in eosinophils and in isolated free extracellular eosinophil granules. We also examine and speculate on the therapeutic relevance of targeting CysLTRs in the treatment of eosinophilic disorders.